Antibiotic-specific differences in the response of Staphylococcus aureus to treatment with antimicrobials combined with manuka honey - Liu, Michael; Lu, Jing; Müller, Patrick; Turnbull, Lynne; Burke, Catherine M.; Schlothauer, Ralf C.; Carter, Dee A.; Whitchurch, Cynthia B.; Harry, Elizabeth J. (Frontiers in Microbiology, 2015)
Skin infections caused by antibiotic resistant Staphylococcus aureus are a significant health problem worldwide; often associated with high treatment cost and mortality rate. Complex natural products like New Zealand (NZ) manuka honey have been revisited and studied extensively as an alternative to antibiotics due to their potent broad-spectrum antimicrobial activity, and the inability to isolate honey-resistant S. aureus. Previous studies showing synergistic effects between manuka-type honeys and antibiotics have been demonstrated against the growth of one methicillin-resistant S. aureus (MRSA) strain. We have previously demonstrated strong synergistic activity between NZ manuka-type honey and rifampicin against growth and biofilm formation of multiple S. arueus strains. Here, we have expanded our investigation using multiple S. aureus strains and four different antibiotics commonly used to treat S. aureus-related skin infections: rifampicin, oxacillin, gentamicin and clindamycin. Using checkerboard microdilution and agar diffusion assays with S. aureus strains including clinical isolates and MRSA we demonstrate that manuka-type honey combined with these four antibiotics frequently produces a synergistic effect. In some cases when synergism was not observed, there was a significant enhancement in antibiotic susceptibility. Some strains that were highly resistant to an antibiotic when present alone become sensitive to clinically-achievable concentrations when combined with honey. However, not all of the S. aureus strains tested responded in the same way to these combinational treatments. Our findings support the use of NZ manuka-type honeys in clinical treatment against S. aureus-related infections and extend their potential use as an antibiotic adjuvant in combinational therapy. Our data also suggest that manuka-type honeys may not work as antibiotic adjuvants for all strains of S. aureus, and this may help determine the mechanistic processes behind honey synergy.